PENGARUH PROJECT BASED LEARNING BERBASIS EKSPLORASI ALAM UNTUK MENINGKATKAN LITERASI NUMERASI SISWA KELAS VIII SMP IT DARUL MUTAQIN - Nugraha, Iqbal; Muhammad Saidun Anwar; Choirudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the Project Based Learning (PjBL) model based on natural exploration on students’ numeracy literacy. The study is motivated by the low level of students’ numeracy skills, particularly in solving contextual mathematical problems. The method used is a quantitative approach with a quasi-experimental design in the form of a pretest-posttest control group design. The population consists of eighth-grade students at SMP IT Darul Mutaqin in the 2025/2026 academic year, with two classes selected through cluster random sampling as the experimental and control groups. Data were collected through pretest and posttest instruments, supported by observation and documentation. The research instruments were tested for validity and reliability prior to use. Data analysis included normality and homogeneity tests, followed by hypothesis testing using a t-test at a significance level of 0.05. The results indicate a significant improvement in numeracy literacy in the experimental group compared to the control group, with a significance value of less than 0.05. These findings suggest that PjBL based on natural exploration is effective in enhancing students’ engagement, critical thinking skills, and contextual problem-solving abilities.